Strategies for improving early nutritional outcomes in children with oesophageal atresia and congenital diaphragmatic hernia. (January 2018) - Fitzgerald, Dominic A.; Kench, Andrea; Hatton, Lucy; Karpelowsky, Jonathan
Abstract: Post-natal growth in surgical lung conditions, such as congenital diaphragmatic hernia and oesophageal atresia with tracheo-oesophageal fistula, is often sub-optimal in the early years of life when lung growth is occurring. Whilst constitutional, behavioural and mechanical factors may contribute to poor feeding and weight gain, there is a common path of management with greater caloric supplementation that may change growth trajectories and potentially lead to better respiratory, anthropometric and cognitive outcomes. We provide simple, single page, feeding supplementation sheets in three age groups: 0–6 months, 6–12 months and 12–24 months that have proven useful for enhancing weight gain in our patients.